Association between Publication Time on Social Networks and Engagement: A Study of Mexican Universities - Valerio, Gabriel; Herrera, Dagoberto J; Rodríguez-Martínez, María del Carmen (Palabra clave, 2014)
Universities are using social media increasingly as communication chan-nels. However, not all universities seem to have a clear strategy that allows them to achieve a broader range. This study shows publication time can affect the impact of a publication. The authors compared the behavior of Fanpage managers to demonstrations of public engagement from the stan-dpoint of their temporary activity cycles. A quantitative methodology was used, based on identifying outstanding publications among 31,590 publi-cations by 28 Mexican universities.
Keywords: Enseñanza superior; Redes sociales